Analysis of 45 Micron Air Filter’s Effect on Car Engine’s Performance (Matic 1500cc) by Using Dynamometer-Bench Test Data Research - Irgi Ahmad Faturrahman; Hadi Pranoto; Nazha Ali Christy (International Journal of Advanced Technology in Mechanical, Mechatronics and Materials, 2022)
There are many racing air filter products on the market with air filter fold gap of 45 microns. However, there has been no research proves that an air filter with 45 microns’ fold gap can increase the performance of a car engine. Based on this, the author is interested in conducting an experimental test analysis of the car engine air filter by modifying the factory standard air filter which has fold gap of 25 microns into an air filter that has fold gap of 45 microns. This study aims to prove whether a 45-micron air filter can increase the performance of a car engine in the form of torque, power, fuel consumption, and mechanical efficiency. The study is conducted by using dynamometer. Analysis of research data uses descriptive statistics with data presentation in the form of tables and graphs. The results of this study indicates that the effect of a 45-micron air filter on a car engine performance is proven to improve car engine performance compared to factory standard air filters with details: torque in car engine increases by 3.05%, power in car engine increases by 1.78%, the specific fuel consumption of the car engine is 1% more efficient, and the mechanical efficiency of the car engine is increased by 0.02%. Based on the research that has been done, it is necessary to do further research regarding the effect of the 45 micron racing air filter on the service life of the piston and valve in the car engine.